Cambios ambientales de épocas históricas en la pampa bonaerense en base a ostrácodos: historia hidrológica de la laguna de Chascomúse (Ameghiniana, 2009)
The paleoenvironmental evolution ofLaguna de Chascomús during the last 500 years is reconstructed based on ostracod assemblages and sedimentologicaland geochemical analyses from sediment cores. The chronology is constrained by one AMS14C date on terrestrial material. The main hydrological and ecological characteristics of the lake are climatically-controlled. Three main expansion - contraction lake cycles have occurred during the last 500years under different hydrological conditions. During periods of relatively higher water availability (endof 15th century - mid 17th century) lake waters were ß-oligohaline and HCO3- dominated; Limnocythere aff.L. sp. staplini was the dominant ostracod species and biodiversity was moderate. During periods of lowerwater availability (beginning of 18th century till mid 19th century, including the Little Ice Age), lake waterswere ?-oligo to mesohaline, with higher salinities and Cl->HCO3-. Cyprideis hartmanni was dominant,and the ostracod assemblages have lower diversity. The paleohydrological evolution is compared to theavailable historical documents. A hydro-ecological conceptual model based on hydrochemistry, hydrologyand ostracod assemblages is proposed to explain the evolution of the lake.